Lower urinary tract symptoms secondary to a vaginal leiomioma the female prostate: case report - Alcaraz, Jennifer E. Reyes; Reyes, Guadalupe Guerrero; Gonzalez, Adrian Gutierrez; Velazquez, Ricardo Hernandez; Maldonado, Karen M. Loya; Cavazos, Omar Treviño; Vazquez, Jose I. Leyva; Cuevas, Sara Y. Saca; Morales, Juan C. Herrera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
This is a case report of lower urinary tract symptoms secondary to a vaginal leiomioma “the female prostate”. A 45-year-old female patient with no significant personal history, sensation of a vaginal foreign body accompanied by lower urinary tract symptoms, on vaginal physical examination with a 7×7 cm deep tumor, increased consistency, not painful, without hemorrhage. Magnetic resonance imaging with hypointense T1 and T2 images, few linear hyperintense areas in T2, homogeneous postgadolinium enhancement 69×66×53 mm, solid tumor dependent on the vaginal vault. Tumor markers CA 19-9: 5.98 U/ml, CEA: 1.09 ng/ml and CA 125: 11.73 U/ml. Open surgery was performed in which a 8×6 cm tumor was found in the vaginal vault dependent on the posterior wall of the vagina. Histopathological report: conventional leiomyoma measuring 9×7.5 cm in long axes, without nuclear atypia. With resolution of symptoms in the lower urinary tract, with normal urinary frequency, without presence of urgency, without urinary incontinence or voiding symptoms. It is important to identify and diagnose lower urinary tract symptoms always, since they could be an initial manifestation of pelvic tumors in which the treatment approach should not be delayed.